1984
DOI: 10.1111/j.1365-2265.1984.tb03444.x
|View full text |Cite
|
Sign up to set email alerts
|

Iodide Organification Defect in a Cold Thyroid Nodule: Absence of Iodide Effect on Cyclic Amp Accumulation

Abstract: A follicular adenoma of the thyroid was 'hot' one hour after 99mTc pertechnetate administration, but 'cold' 24 h after 131I iodide administration. Incubation of the tissue in vitro demonstrated a defect in iodide binding to proteins that was abolished by addition of an H2O2 generating system. In this tissue iodide failed to inhibit TSH-induced cyclic AMP accumulation. The results show that iodide oxidation is required for its inhibitory action on cyclic AMP accumulation in human thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The following facts suggest that this also applies to intact follicles. 1) Exogenous supply of H 2 O 2 greatly enhances iodination in thyroid slices (3,24). 2) TSH, which enhances iodination in dog thyroid, also activates H 2 O 2 generation in this system (5).…”
Section: Discussionmentioning
confidence: 98%
“…The following facts suggest that this also applies to intact follicles. 1) Exogenous supply of H 2 O 2 greatly enhances iodination in thyroid slices (3,24). 2) TSH, which enhances iodination in dog thyroid, also activates H 2 O 2 generation in this system (5).…”
Section: Discussionmentioning
confidence: 98%
“…It should allow to demonstrate the genetic lesion of this system in iodination defects observed in congenital hypothyroidism, thyroid cold adenomas, and thyroid cancer with normal thyroperoxidase (43,44). The close proximity of thyroperoxidase and ThOX at the apical pole of thyrocytes suggests that autoimmune reactions leading to the generation of autoantibodies directed against the former might spread to the latter in Hashimoto's thyroiditis or Graves' diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies performed in two cases (6,21) suggested that the defect does not reside in thyroid peroxidase but in the H 2 O 2 generating system.…”
Section: Discussionmentioning
confidence: 96%
“…Because all the follicular carcinomas showed the trapping-only phenomenon, the authors suggested that this pattern might be associated with follicular cancer. However, these data were not generally confirmed in subsequent studies where the majority of patients had benign nodules (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Therefore, the actual prevalence of the trapping-only phenomenon and its possible association with thyroid malignancy is still an open question.…”
Section: Introductionmentioning
confidence: 86%